Three month follow up of an alcohol addiction program - Türkcan, Ahmet; Coşkun, Beyhan; İlem, Esra; Çakmak, Duran (Journal of Dependence, 2001)
Object: In this study three months follow up of an alcohol addiction program examined.Method: 90 patients, who are accepted to join a program of 8 inpatient sessions and 4 outpatient sessions, examined. Total of 12 cognitive behavioral psychotherapy sessions was conducted to the patients who were diagnosed as an alcohol addict according to DSM-IV criteria. Outpatient interaction groups were conducted with the patients who completed at least 10 sessions of cognitive behavioral therapy. 65 patients could be followed for three months by telephone contacts, with intervals of at least once a month. Those 65 patients classified according to slip, lapse, relapse and remission.Results: At the end of three month period 72.3% of 65 patients was in remission and 27.7% relapsed. Patients in remission, were more likely engaged in outpatient treatment than the patients who were relapsed (p < 0.05) and number of sessions engaged in outpatient treatment were higher (p
Keywords: Alcohol; addiction; psychotherapy